Mindfulness in persons with anorexia nervosa and the relationships between eating disorder symptomology, anxiety and pain. Issue 5 (3rd September 2021) - Dunne, Julie P.; Shindul-Rothschild, Judith; White, Laura; Lee, Christopher S.; Wolfe, Barbara E.
ABSTRACT: Mindfulness is useful for some psychiatric illnesses, but limited research exists among persons with anorexia nervosa (AN). This study aimed to determine the relationship between mindfulness, eating disorder symptomology and indicators of health in women with AN ( n = 59) entering residential treatment. Participants completed a self-administered survey, including the Cognitive Affective Mindfulness Scale and other measures. Additional data from medical records were collected. Greater mindfulness was associated with less eating disorder symptoms ( p = .049). This relationship was most profound in individuals with AN, including restrictive and binge-purge subtypes compared to individuals with atypical AN (interaction p -value = 0.044). Greater mindfulness was significantly associated with less shape ( p = .023) and weight concern ( p = .047). Expectedly, anxiety was inversely associated with eating disorder symptoms ( p = .001). Greater pain was associated with less eating disorder symptoms ( p = .024). Overall, mindfulness may be a protective factor against some eating disorder symptomology.